2015
DOI: 10.1016/j.mayocp.2015.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Motor and Nonmotor Circuitry Activation Induced by Subthalamic Nucleus Deep Brain Stimulation in Patients With Parkinson Disease

Abstract: Objective To test the hypothesis suggested by previous studies that subthalamic nucleus (STN) deep brain stimulation (DBS) in patients with PD would affect the activity of both motor and non-motor networks, we applied intraoperative fMRI to patients receiving DBS. Patients and Methods Ten patients receiving STN DBS for PD underwent intraoperative 1.5T fMRI during high frequency stimulation delivered via an external pulse generator. The study was conducted between the dates of January 1, 2013 and September 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 67 publications
6
60
0
1
Order By: Relevance
“…We found STN DBS enhanced glucose metabolism in the occipital and parietal cortices, whereas it inhibited the glucose metabolism in the frontal cortex and cerebellar cortex. These findings suggest that STN DBS intervenes in the CSTC circuitry, including deactivating the premotor cortex and cerebellum, and activating the somatosensory cortex and related cerebellocortical pathways, which is consistent with a previous study [4,8,9,10]. PD with autonomic failure has been reported to present a markedly reduced glucose metabolism in the occipital cortex, inferior parietal cortex and superior parietal cortex [4].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found STN DBS enhanced glucose metabolism in the occipital and parietal cortices, whereas it inhibited the glucose metabolism in the frontal cortex and cerebellar cortex. These findings suggest that STN DBS intervenes in the CSTC circuitry, including deactivating the premotor cortex and cerebellum, and activating the somatosensory cortex and related cerebellocortical pathways, which is consistent with a previous study [4,8,9,10]. PD with autonomic failure has been reported to present a markedly reduced glucose metabolism in the occipital cortex, inferior parietal cortex and superior parietal cortex [4].…”
Section: Discussionsupporting
confidence: 91%
“…However, the discoveries concerning regional glucose metabolic changes of PD patients after STN DBS are still not concordant. Besides, PD-related regional metabolic covariance pattern (PDRP) network analysis classified idiopathic PD with 84% sensitivity and 97% specificity, helping to differentiate PD from atypical parkinsonism such as multiple system atrophy and progressive supranuclear palsy [7]; this indicates its potential usefulness in diagnosing PD and displays PDRP as a promising biomarker to track disease progression and monitor therapeutic interventions in PD [8]. …”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown connectivity between limbic areas of cortex and STN (Brunenberg et al ., 2012). Intraoperative fMRI imaging of PD patients during STN stimulation demonstrated simultaneous activation of limbic regions (cingulate and insular cortices) (Knight et al ., 2015). Similar studies using PET showed increased activation during STN stimulation in the dorsolateral prefrontal cortex bilaterally (Haegelen et al ., 2005) and the anterior cingulate (Sestini et al ., 2002).…”
Section: Stn Involvement In Limbic Functionmentioning
confidence: 99%
“…In order to investigate the global circuit involvement during DBS, we have developed a technique that combines DBS and functional MRI (fMRI), as a means of tracing brain circuitry and testing the modulatory effects of electrical stimulation on a neuronal network (Knight et al, 2015; Min et al, 2014; Min et al, 2012). Using this setup, we aimed to trace fornix DBS-induced global neural activity.…”
Section: Introductionmentioning
confidence: 99%